Avaliação e aprendizagem de alunos surdos em uma escola pública de Manaus - Silva, Amanda Souza da (Brasil, 2022)
This research is located in Applied Linguistics field and deals with the evaluation of deaf students. Learning assessment has been a broad field of research with different perspectives, aiming a more specialized angle applying a qualitative nature. The study intent to reflect about evaluation and the literacy assessment in the deaf education context. The specific objectives demonstrate how teachers of the deaf students apply assessment tools for teaching Brazilian Sign Language “Libras” as L1, list instruments that are proposed and used in the deaf evaluation. The research methodology is based on qualitative research (ANDRÉ, 2013; PERREIRA, 2018) and the case study method (YIN, 2001). The research context was applied at the Augusto Carneiro dos Santos State School, as research instruments questionnaires were used, with five participants between teachers and school students, the data analysis applied was proposed by Bardin (2011). The results achieved are that the evaluation is in constant alternation, in view of the results it is concluded that the evaluation must be more specific, that the instruments used need alterations. In addition, the research should be continuous and the literacy assessment in languages must be more explored and researched.